Reproduction and condition of the scallop Adamussium colbecki (Smith 1902), the sea-urchin Sterechinus neumayeri (Meissner, 1900) and the sea-star Odontaster validus Koehler, 1911 at Terra Nova Bay (Ross Sea): different strategies related to inter-annual variations in food availability - CHIANTORE, MARIACHIARA; CATTANEO VIETTI, RICCARDO; ELIA L.; GUIDETTI M.; ANTONINI M. (Polar Biology, 2002)
Soft-bottom zoobenthic communities at Terra Nova Bay down to 100 m depth are mainly characterised by the presence of three species, generally occurring together and reaching high values of density: the scallop Adamussium colbecki (Smith 1902), the echinoid Sterechinus neumayeri (Meissner 1900) and the asteroid Odontaster validus Koehler 1911. These three species have a planktotrophic larval behaviour, but differ in terms of extent of gametogenic cycle and in feeding behaviour. The aim of this work is to give a first account of their reproductive conditions at Terra Nova Bay, comparing two following summer seasons, characterised by quite different ice-coverage and, consequently, food availability in the water column. The comparative analysis of the data evidences strong inter-annual differences in the scallop, a suspension-feeding species. In contrast, no significant changes were found in the two echinoderms, suggesting that a 2-year oogenic cycle, coupled with the opportunistic feeding behaviour, allow successful management of inter-annual shortcomings in food supply. On a latitudinal perspective, the comparison between data from McMurdo Sound and Terra Nova Bay shows small (for the echinoderms) or greater (for the scallop) geographical shifts in spawning occurrence.